Photon quantum entanglement in the MeV regime and its application in PET imaging - D. P. Watts; J. Bordes; J. R. Brown; A. Cherlin; R. Newton; J. Allison; M. Bashkanov; N. Efthimiou; N. A. Zachariou (Nature Communications, 2021)
Gamma photons used in positron emission tomography are predicted to be produced in an entangled state. Here, the authors simulate the effects of entanglement and test them through comparison with experimental data from a PET demonstrator apparatus, showing the potential gains in background suppression.